The Place and Importance of Playgrounds in Child Development - Merve ÜNAL (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Education is an activity that is not restricted to the school areas, sometimes goes beyond the school walls. Similar to schools, various institutions or establishments like playgrounds, libraries, and museums also take place in educational and/or instructional process. Among these places, playgrounds can be regarded as critically important in terms of discharging children’s high energy, positive self (ego) development, exploring skills, self esteem and success of children, and also cognitive, physical and psychological development of children. We need playgrounds to enhance these skills and to provide an option for our children to learn new things. In this study we will argue importance and kinds of playgrounds